Philosophy of ontology, epistemology, and axiology of anti-corruption education - Zulaiha, Aida Ratna (Integritas: Jurnal Antikorupsi, 2025)
Corruption in Indonesia is a serious offense with widespread social and economic impacts. Consequently, anti-corruption education (PAK) is crucial in shaping individual integrity from an early age. This article examines the philosophy of anti-corruption education by exploring its fundamental values, implementation methods, benefits, and objectives through the lenses of ontological, epistemological, and axiological educational philosophy. The research employs a qualitative literature review approach to analyze relevant theories, existing policies, and empirical studies. Findings indicate that, from an ontological perspective, PAK focuses on character development centered on ten integrity values: honesty, responsibility, fairness, trustworthiness, courage, discipline, empathy, perseverance, independence, and respect, which constitute the essence of character education. Epistemologically, the implementation method of PAK involves integrating anti-corruption values into the learning curriculum, alongside the development of an integrity-based educational ecosystem that encompasses individuals within the ecosystem and the governance of educational institutions. From an axiological perspective, PAK aims to cultivate a culture of "refusing to engage in corruption," ensuring that individuals not only understand the concept of corruption but also develop a strong commitment to avoiding it. This research also encourages PAK to be implemented through a structured, gradual, and sustainable curriculum aligned with moral development stages, involving all actors within the educational ecosystem to effectively achieve PAK’s goal of fostering an integrity-driven, anti-corruption generation.